The dosimetric effect of residual breath-hold motion in pencil beam scanned proton therapy – An experimental study. (May 2019) - Gorgisyan, Jenny; Lomax, Antony J.; Rosenschold, Per Munck af; Persson, Gitte F.; Krieger, Miriam; Colvill, Emma; Scherman, Jonas; Gagnon-Moisan, Francis; Egloff, Martina; Fattori, Giovanni; Engelholm, Svend Aage; Weber, Damien C.; et al.
Highlights: Intra-breath-hold motion was investigated in PBS proton therapy. 3D-printed tumours and real motion data were input to an anthropomorphic phantom. SFUD treatment plans were shown to be robust to motion. IMPT treatment plans were less robust and should be used with caution. Abstract: Background and purpose: Motion management in the treatment of lung cancer is necessary to assure highest quality of the delivered radiation therapy. In this study, the breath-hold technique is experimentally investigated for pencil beam scanned (PBS) proton therapy, with respect to the dosimetric effect of residual breath-hold motion. Material and methods: Three-dimensional (3D)-printed tumours extracted from CT scans of three patients were inserted into a dynamic anthropomorphic breathing phantom. The target was set up to move with the individual patient's tumour motion during breath-hold as previously assessed on fluoroscopy. Target dose was measured with radio-chromic film, and both single field uniform dose (SFUD) and intensity-modulated proton therapy (IMPT) plans were delivered. Experiments were repeated for each patient without any motion, to compute the relative dose deviation between static and breath-hold cases. Results: SFUD plans showed small dose deviations between static and breath-hold cases, as evidenced by the gamma pass rate (3%, 3 mm) of 85% or higher. Dose deviation was more evident for IMPT plans, with gamma pass rate reduced to 50–70%. Conclusions: The breath-hold technique is robust to residual intra-breath-hold motion for SFUD treatment plans, based on our experimental study. IMPT was less robust with larger detected dose deviations.